Postural Control Strategies and Balance-Related Factors in Individuals with Traumatic Transtibial Amputations - Kolářová, Barbora; Janura, Miroslav; Svoboda, Zdeněk; Kolář, Petr; Tečová, Dagmar; Elfmark, Milan (Sensors (Basel, Switzerland), 2021)
Mechanisms behind compromised balance control in people with transtibial amputation need to be further explored, as currently little is known specifically about postural control strategies in people with traumatic transtibial amputation (tTTA). The aim of this study is to assess automatic and voluntary postural control strategies in individuals with unilateral tTTA compared to those in control subjects and to define the effect of balance-related factors on these strategies. Automatic posture reactions and volitional motion toward given direction using standardized posturographic protocols (NeuroCom) of the Motor Control Test (MCT) and Limits of Stability (LOS) were assessed in eighteen participants with tTTA and eighteen age-matched controls. Compared to the controls, the participants with tTTA bore less weight on the prosthetic leg (p < 0.001) during the MCT and had reduced inclination toward the prosthetic leg (p < 0.001) within the LOS. In the tTTA group, the weight-bearing symmetry and the inclination toward the prosthetic leg (p < 0.05) was positively correlated with prosthesis use duration (p < 0.05). The current study indicates that decreased utilization of the prosthetic leg in tTTAs represents adaptive postural control strategy, but as prosthesis use duration increased, the engagement of the prosthetic leg improved.